Parental involvement in raising Grade 12 achievement in South African rural secondary schools - Triegaardt, Paul Karel; Monamoledi, Veronica Mapaseka (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2021)
The South African Schools Act No.84 of 1996 obliges parents to bring their children to school from the first day of their schooling. This means that the legislation gives parents the right to be fully involved in their children’s education for better academic achievement. This study examined parental involvement in raising Grade 12 achievement in South African rural schools. A qualitative study was done at three secondary schools in the Mkhuhlu circuit in the Bohlabela region of the Mpumalanga Province. Data were collected in the form of interviews from the principal, teachers, parents and Grade 12 learners at each of the three schools. The study found that at all three schools, parents were not aware of their importance to motivate learners to learn, the need to attend school regularly and the development of their own literacy skills to raise the results in Grade 12. Therefore, the study recommends that parents must be empowered by both teachers and principals in order for them to be able to execute their roles effectively.